Effects of Facilitation vs. Exhibit Labels on Caregiver-Child Interactions at a Museum Exhibit - Letourneau, Susan M.; Meisner, Robin; Sobel, David M. (Frontiers in Psychology, 2021)
In museum settings, caregivers support children’s learning as they explore and interact with exhibits. Museums have developed exhibit design and facilitation strategies for promoting families’ exploration and inquiry, but these strategies have rarely been contrasted. The goal of the current study was to investigate how prompts offered through staff facilitation versus labels printed on exhibit components affected how family groups explored a circuit blocks exhibit, particularly whether children set and worked toward their own goals, and how caregivers were involved in children’s play. We compared whether children, their caregivers, or both set goals as they played together, and the actions they each took to connect the circuits. We found little difference in how families set goals between the two conditions, but did find significant differences in caregivers’ actions, with caregivers in the facilitation condition making fewer actions while using the exhibit, compared to caregivers in the exhibit labels condition. The findings suggest that facilitated and written prompts shape the quality of caregiver-child interactions in distinct ways.